1993
DOI: 10.1677/joe.0.1390395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone and an antiserum to rat growth hormone on serum IGF-I and muscle protein synthesis and accretion in the rat

Abstract: Rats were injected twice daily for up to 10 days with GH or with a polyclonal antiserum to rat GH, commencing at 21-22 days of age. Administration of bovine or human GH (1mg/day) improved whole body growth rates by 22% and 29% respectively. Plantaris muscle mass was also increased, by 7 and 14% respectively. Anti-GH injected twice daily resulted in a 7% decrease in body weight at 4 days and a 10% reduction by 10 days. Similar decreases were observed in the total protein content of plantaris and soleus muscles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
2
3
1
Order By: Relevance
“…It is now known that peripheral tissues such as skeletal muscle and chondrocytes can synthesise IGF-I and that the response of the peripheral tissues to GH can be mediated in a paracrine and an autocrine manner through IGF-I produced in situ. Our observations in large and medium-sized dogs, like those in young rats (Palmer et al 1993), do not support the concept that total plasma IGF-I plays a crucial role as an endocrine mediator of GH action.…”
Section: Discussioncontrasting
confidence: 99%
“…It is now known that peripheral tissues such as skeletal muscle and chondrocytes can synthesise IGF-I and that the response of the peripheral tissues to GH can be mediated in a paracrine and an autocrine manner through IGF-I produced in situ. Our observations in large and medium-sized dogs, like those in young rats (Palmer et al 1993), do not support the concept that total plasma IGF-I plays a crucial role as an endocrine mediator of GH action.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we have previously shown that administration of our anti-rGH inhibits growth in rats (Flint & Gardner 1993); this is consistent with other studies which have demonstrated that serum GH levels can be lowered by treatment of rats with antisera against GH-releasing hormone (Tannenbaum & Ling 1984, Wehrenberg et al 1992, resulting in inhibition of growth. The reduction in serum insulin levels induced by immunoneutralisation of serum GH was consistent with previous observations and may be attributable to the decrease in food intake which occurs as a consequence of anti-rGH treatment (Palmer et al 1993).…”
Section: Discussionsupporting
confidence: 91%
“…This is compatible with the equivalent proportional decreases in each of the three muscles studied. As in a previous study (Palmer et al 1993), effects on the three hind-limb muscles were of similar magnitude but this does not necessarily indicate that the mechanism of GH action is the same on all muscles. Whilst two of the muscles, gastrocnemius and plantaris, are of a fast oxidative fibre-type typical of the bulk of the body musculature and responded to anti-GH with a reduced rate of protein synthesis, the soleus contains a higher proportion of slow oxidative glycolytic fibres and responded to anti-rGH principally by an increase in the rate of degradation (Palmer et al 1993).…”
Section: Discussionsupporting
confidence: 45%
“…Furthermore, sys¬ temic administration of IGF-I to hypophysectomized rats is not as effective as GH in stimulating longitudinal growth (Skottner et al 1987). In our short-term studies, involving injection of anti-rGH into young weaned rats, the obser¬ vation that injection of anti-rGH for up to 10 days reduced growth rate of the whole body and the hind-limb muscles (Palmer et al 1993) and bone (Loveridge et al 1994) without affecting plasma IGF-I levels suggests that, in the young prepubertal rat, changes in total plasma IGF-I may not be a prerequisite for all the metabolic effects of GH.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation